Differentiation of Two Groups of Corynebacterium acnes - Voss, J. G. (1970)
One hundred and forty-three strains of Corynebacterium acnes, isolated from human skin and acne lesions, were compared with three strains of Propionibacterium acnes from the American Type Culture Collection. The 146 organisms could be separated into two groups. Members of the larger group (129 strains) hydrolyzed gelatin and usually produced indole, Gel-In(+), but were unable to ferment trehalose, maltose, or sucrose, TMS(−). The deoxyribonucleic acid from selected strains of this group had an average guanosine + cytosine (GC) content of 60.5%. The members of the smaller group (17) were Gel-In(−), TMS(+), and the deoxyribonucleic acid had an average GC content of 63.9%. Studies with absorbed and unabsorbed antisera to the smaller group showed that although there were antigens shared by the two groups, it was possible to distinguish them serologically. Members of each group produced propionic acid. The principal fatty acid component of members of each group was iso-C(15) fatty acid. Seventy per cent of the Gel-In(+) strains were lysed by phage 174, whereas only one of 15 Gel-In(−) strains was lysed. Pending further information on the genetics of the two groups, those Gel-In(−), TMS(+) strains are tentatively designated C. acnes, group II.